Pengaruh Penggunaan Media Pembelajaran Garis Bilangan terhadap Hasil Belajar Matematika - Nurul Karimah (JKPM (Jurnal Kajian Pendidikan Matematika), 2016)
The aim of the experiment research is to know the effect of Using Media Instructional the number line on mathematics achievement. Research design used true experimental design in the form of posttest only control design. The research was conducted in the fourth grade of Islamic Elementary School (Madrasah Ibtidaiyah Al-Khairiyah) academic year 2013/2014. Sample was taken randomly, there are two groups as sample, they are experiment group (class IV A) and control group (class IV B). After giving different treatment for each group, then giving the posttest with the instrument that consist of 22 items in multiple choices with 4 alternative answers. The instrument that was used in this research has been tested, and all the items were valid and reliable. Inferentially, data analysis of the research used  test, normality and homogenity test has been done. The result research shows that there is the significant effect of using media instructional of number line on mathematics achievement, especially on the standard competence of addition and subtraction integers.